Hand hygiene: are WHO Framework scores consistent with hand rub consumption data? A regional study. (30th September 2020) - Garlasco, J; Vicentini, C; Emelurumonye, I N; Quattrocolo, F; D'Alessandro, G; Zotti, C M
Abstract: Background: Hand hygiene represents one of the most effective measures to prevent infection transmission in healthcare facilities and may reduce healthcare-associated infections by up to 15-30%. In Piedmont (a region in North-West Italy), hand hygiene compliance is routinely monitored through the WHO Hand Hygiene Self-Assessment Framework (HHSAF) and each hospital is also required to provide data about alcohol-based hand rub (ABHR) consumption as part of the regional performance indicator surveillance system. The aim of this study is to assess whether these two systems yield consistent results, i.e. whether numerical data matches the self-reported status of hand hygiene compliance. Methods: For the years 2015-2018, data on ABHR consumption (in millilitres per patient-day, ml/PD) were collected annually at a facility level (40 hospitals) and then aggregated according to the corresponding local health unit/hospital unit, whereas the HHSAF scores were collected at a health/hospital unit level (18 units). The analysis was performed through logistic regression, by taking the WHO HHSAF score (continuous variable) as predictor and ABHR consumption as response variable, dichotomously considered as "low" or "high" (respectively below or above the 20 ml/PD threshold commonly accepted for good practice in hand hygiene). Results: This study found that a high level of ABHR consumption is more likely to be observed in hospitals/health units with higher HHSAF scores, with a 1.14-fold increase in the odds for every 10-point increase in the HHSAF score. Despite the limited number of observations due to data aggregation, the result reached borderline statistical significance (p = 0.05). Conclusions: The ABHR consumption surveillance provides feedback heading in the same direction as the results of the HHSAF, therefore the two surveillance systems are consistent. These findings provide further support for the validity of the HHSAF score as a reasonable predictor of hand hygiene compliance. Key messages: The WHO Hand Hygiene Self-Assessment Framework score is a reliable predictor of hand hygiene compliance, as a high hand rub consumption is more likely to occur in hospitals with higher HHSAF score. Surveillance through the WHO HHSAF should be encouraged, along with alcohol-based hand rub (ABHR) measurement, and these results should be used to guide action plans to promote hand hygiene.